(untitled) - Capel, Will (Thành phố Hồ Chí Minh, 2014)
This third edition has been fully updated to reflect today's business world with new topics and example sentences. Armed with this book, you will learn the words you need for effective business communication. Suitable for intermediate/upper-intermediate learners of English (CEF level B1-B2), Collins Business Vocabulary in Practice presents business words in context and exercises to help you remember them. New words are introduced using Collins COBUILD definitions and supported by examples of real English from the Collins corpu
Keywords: Vocabulary,Từ vựng,English language,Tiếng Anh; Business English,Tiếng Anh thương mại